A research about Health promoting activities (lifestyle) at employees - MH Baghianimoghadam; MH Ehrampoush; N Ardian; T Soltani (طب کار)
Background: Health promoting activities (Lifestyle) is an indicator of the health of the bilateral relationship between physical and mental health and can be used as a predictor of mental health. It also aimed at comparing their different lifestyles. Methods: Using random sampling, 400 office staff and workers in Yazd were selected to participate in this descriptive analytical study. A questionnaire used to collect data included two sections: demographic section and standard questionnaire of HPLP II to evaluate lifestyle. The demographic characteristics and lifestyle of different levels by HPLP II: The difference between life style and 6 subscales in office staff and labor were three levels. Data analysis were done using SPSS program for windows (v. 16) by conducting several statistical operations such as t-test, chi-square, one-way ANOVA, pearson correlation coefficient, and linear regression. Results: It was indicated that there were significant difference in lifestyle and its six subcategories comparing workers. Concerning both groups, the highest among these subcategories belonged to spiritual growth and interpersonal relations and the lowest scores belonged to physical activities, different social, economic and cultural impact on the lifestyle of employees. Conclusion: In spite of the increase in blue collar workers’ wages, it seems that besides workplace, the social, economic, and cultural differences affect the differences in lifestyles of white collar and blue collar workers.